Functional characterization of cardiac actin mutants causing hypertrophic (p.A295S) and dilated cardiomyopathy (p.R312H and p.E361G) - Hassoun, Roua; Erdmann, Constanze; Schmitt, Sebastian; Fujita-Becker, Setsuko; Mügge, Andreas; Schröder, Rasmus R.; Geyer, Matthias; Borbor, Mina; Jaquet, Kornelia; Hamdani, Nazha; Mannherz, Hans Georg (International journal of molecular sciences, 2022)
Human wild type (wt) cardiac α-actin and its mutants p.A295S or p.R312H and p.E361G correlated with hypertrophic or dilated cardiomyopathy, respectively, were expressed by using the baculovirus/Sf21 insect cell system. The c-actin variants inhibited DNase I, indicating maintenance of their native state. Electron microscopy showed the formation of normal appearing actin filaments though they showed mutant specific differences in length and straightness correlating with their polymerization rates. TRITC-phalloidin staining showed that p.A295S and p.R312H exhibited reduced and the p.E361G mutant increased lengths of their formed filaments. Decoration of c-actins with cardiac tropomyosin (cTm) and troponin (cTn) conveyed Ca2+-sensitivity of the myosin-S1 ATPase stimulation, which was higher for the HCM p.A295S mutant and lower for the DCM p.R312H and p.E361G mutants than for wt c-actin. The lower Ca2+-sensitivity of myosin-S1 stimulation by both DCM actin mutants was corrected by the addition of levosimendan. Ca2+-dependency of the movement of pyrene-labeled cTm along polymerized c-actin variants decorated with cTn corresponded to the relations observed for the myosin-S1 ATPase stimulation though shifted to lower Ca2+-concentrations. The N-terminal C0C2 domain of cardiac myosin-binding protein-C increased the Ca2+-sensitivity of the pyrene-cTM movement of bovine, recombinant wt, p.A295S, and p.E361G c-actins, but not of the p.R312H mutant, suggesting decreased affinity to cTm.
This article belongs to the Section Molecular Biology
Gesehen am 13.07.2022